Estudio de las radiaciones electromagnéticas producidas por las cocinas de inducción en los seres humanos - Gualotuña Paltan, Jeferson Alexander (2019)
The present research is intended to study of electromagnetic radiations produced by induction stoves commercialized in Ecuador, those use magnetic principle, allowing by this way to induce currents to the human beings that are in constantly contact harming their health exceeding established limits from international regulations. The research consists in knowing the components and operation of the induction stoves to design a measurement methodology with the helping of EMF 450 equipment, in order to quantify the electromagnetic radiations produced by different brands with greater commercialization in the country observing if they comply with allowed ranges. Possible damages caused by electromagnetic radiation will be published, trying to prevent and guarantee the welfare of vulnerable people who are in contact with this type of electrical appliances. The obtained data according to established methodology by regulations of International Electrotechnical Commission (IEC-62233), the devices are into established parameters, however acording to the researching process proposed by the authors the radiation levels exceed the limits.